2010
DOI: 10.1091/mbc.e09-02-0133
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Liver Steatosis and Lipid Droplet Formation in ATF6α-Knockout Mice Burdened with Pharmacological Endoplasmic Reticulum Stress

Abstract: We burdened mice with intraperitoneal injection of the endoplasmic reticulum stress-inducing reagent tunicamycin, and found that wild-type mice were able to recover from the insult, whereas ATF6α-knockout mice exhibited liver dysfunction and steatosis. Our results establish links between endoplasmic reticulum stress, lipid metabolism and steatosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
236
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(265 citation statements)
references
References 62 publications
22
236
1
4
Order By: Relevance
“…Although Atf6α −/− mice display no apparent developmental phenotype under normal growth conditions, Atf6α deletion severely impairs liver function and prolongs steatosis compared with wild-type mice upon ER stress (Wu et al 2007;Rutkowski et al 2008;Yamamoto et al 2010). This might result from prolonged CHOP expression in response to chronic UPR activation and consequent suppression of C/EBPα (Rutkowski et al 2008) as well as reduced expression of chaperones and ERAD functions (Wu et al 2007;Yamamoto et al 2010). On the other hand, forced expression of the functionally active nuclear fragment of ATF6 in zebrafish causes fatty liver (Howarth et al 2014), suggesting that fine-tuning of ATF6α may be important to prevent liver steatosis.…”
Section: Atf6αmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Atf6α −/− mice display no apparent developmental phenotype under normal growth conditions, Atf6α deletion severely impairs liver function and prolongs steatosis compared with wild-type mice upon ER stress (Wu et al 2007;Rutkowski et al 2008;Yamamoto et al 2010). This might result from prolonged CHOP expression in response to chronic UPR activation and consequent suppression of C/EBPα (Rutkowski et al 2008) as well as reduced expression of chaperones and ERAD functions (Wu et al 2007;Yamamoto et al 2010). On the other hand, forced expression of the functionally active nuclear fragment of ATF6 in zebrafish causes fatty liver (Howarth et al 2014), suggesting that fine-tuning of ATF6α may be important to prevent liver steatosis.…”
Section: Atf6αmentioning
confidence: 99%
“…First, the expression levels of TFs need to be properly regulated at the appropriate level. For example, the absence of ATF6α causes liver steatosis upon ER stress (Wu et al 2007;Rutkowski et al 2008;Yamamoto et al 2010), whereas overexpression of the active form of ATF6α in zebrafish livers causes fatty liver due to lipid accumulation (Howarth et al 2014). There appears to be an optimum of expression versus toxicity.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Mice impaired in UPR signaling or with an intact UPR but compromised ER protein folding developed profound hepatic steatosis upon challenge with the ER stress-inducing agent tunicamycin (TM) (23,24). This steatosis was accompanied by prolonged suppression of the expression of a host of metabolic genes.…”
Section: Atf4mentioning
confidence: 99%
“…This seems likely due to the induction of glucose-dependent XBP-1s in addition to ER stress (29). Previous KO gene studies showed that the absence of ER stress-sensing proteins, including ATF6a, caused hepatic steatosis (30,31). It was also reported that ER stress-induced hepatic steatosis was alleviated by the administration of recombinant FGF21 protein (9).…”
Section: Discussionmentioning
confidence: 97%